ASSOCIATION OF LIPID LEVELS DURING GESTATION COMPLICATED WITH GESTATIONAL DIABETES MELLITUS AND EARLY PREDICTION OF GESTATIONAL DIABETES MELLITUS BY FIRST TRIMESTER LIPID VALUES - Milinčić, Miloš (Medicinski podmladak, 2024)
Pregnancy induces intricate physiological changes, including alterations in lipid profiles crucial for fetal development. The transition from an anabolic to a catabolic phase in the third trimester reflects increasing insulin resistance, facilitating lipid breakdown for fetal energy. Physiological pregnancy exhibits significant lipid profile changes, with dyslipidemia linked to negative effects on maternal and fetal health. Dyslipidemia in pregnancy correlates strongly with cases of pregnancy-related high blood pressure and diabetes. Gestational diabetes mellitus (GDM) introduces distinctive lipid alterations, including elevated triglycerides (TG) and low-density lipoprotein particles. Mixed dyslipidemia in GDM, exceptionally high TG, and reduced levels of high-density lipoprotein cholesterol (HDL-C) are linked to negative perinatal outcomes, emphasizing the importance of lipid profile assessment. Evaluating lipid profiles, especially TG levels, in early pregnancy proves valuable in predicting GDM. The ratio of triglycerides to high-density lipoprotein cholesterol (TG/HDL-C) shows potential as a predictive marker for GDM, demonstrating commendable sensitivity and specificity. Elevated TG levels, even before 28 weeks, increase GDM risk, emphasizing the role of lipid markers in early detection. Early predictions of GDM through plasma lipid profiling offer a promising avenue for enhancing antenatal care. While standardized markers and thresholds require further research, integrating lipid profiles into routine screenings may optimize GDM management, ultimately benefiting both the mother and fetus.